(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
In this paper we introduce the concept of an interval valued  ,  -fuzzy H v -ideal of an H v -ring, which is a generalization of a fuzzy H v -ideal of an H v -ring. Also we introduce interval valued   , q-fuzzy H v -ideal and some of their properties. Mathematics Subject Classification 20N20